Seismic Evaluation of the RC Moment Frame Structure using the Shake Table - Ullah, H.; Rizwan, M.; Fahad, M.; Shah, S. A. A. (Engineering, Technology & Applied Science Research, 2021)
This paper presents the findings of an experimental investigation on a reinforced concrete frame structure (ordinary moment resistant frame). The test model was subjected to lateral excitation employing the 1994 Northridge earthquake accelerogram. The reinforced concrete test model was fabricated in 1:3 reduced scale acquiring dimensional similarities. The utilized ingredient mix ratio was 1:1.65:1.75 and the water to binder ratio was 0.47. The dynamic characteristics (natural frequency and elastic viscous damping) were calculated using the free vibration record. Story shear, drift, and displacement profiles were drawn using multiple excitation records along with damage patterns and capacity curves. The natural frequency of 2.47Hz was calculated for the test specimen, which is equivalent to 1.41Hz for the prototype. Structural damping (elastic viscous) of 12.36% was calculated for the prototype.